EU-NATO Partnership in 2017–2018 – Towards a New Model of Effective Response to Threats - Przybylska-Maszner, Beata (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2019)
The purpose of this article is to understand the factors determining the state of European Union-NATO relations since 2017. Current determinants of these relations are discussed alongside the structures of interinstitutional links between the two organizations. In order to properly investigate the research problems identified, qualitative selection of sources in the form of legal acts and ‘soft law’ documents of the organizations concerned has been em- ployed. The research questions addressed in the analysis concern the sources and dynamics of changes in these relations. The answers are based on an examination of the determinants of behavior of participants in the decision-making process of both organizations. The article is based on the assumption that, in the period analyzed, the hitherto principle of correlation of tasks based on the two organizations mutually complementing their respective potentials, has been modified. Recurrent situations calling for a joint and multidimensional response to cri- ses have considerably widened the potential scope of strategic commitment of both partners and contributed to their links becoming stronger. Intensified activities aimed at developing the EU’s CSDP have occurred while political disputes regarding the role of both entities in the new balance of strategic forces have significantly multiplied. European limitations on ex- ercising an actual military influence in the region impede the chances of effective cooperation between the two entities.

Celem artykułu jest wskazanie czynników warunkujących stan relacji Unia Europejska – NATO po roku 2017. Przedstawione zostały istniejące determinanty tych relacji, jak i istniejące struktury powiązań międzyinstytucjonalnych obu organizacji. W celu właściwego rozpatrzenia wskazanych problemów badawczych zastosowano dobór jakościowy źródeł w postaci wybranych aktów prawnych i dokumentów typu soft law omawianych organizacji. Pytania badawcze stawiane w prowadzonej analizie dotyczą źródeł i przejawów dynamiki zmian w relacjach. Odpowiedź na nie udzielona została w oparciu o ukazane determinanty zachowań uczestników procesu decyzyjnego omawianych organizacji. W artykule oparto się na założeniu, iż w oma- wianym okresie dotychczasowa zasada korelacji zadań UE–NATO oparta na uzupełnianiu potencjału obu organizacji uległa modyfikacji. Powtarzające się sytuacje wymagające wspólnego i wielowymiarowego reagowania na kryzys znacząco zwiększyły obszar możliwego zaangażowania obu strategicznych partnerów i przyczyniły się do wzmocnienia istniejących powiązań. Intensyfikacja działań na rzecz rozwoju WPBiO UE występuje w okresie, gdy znacząco wzrosła liczba sporów politycznych dotycząca roli obu podmiotów w nowym układzie sił strategicznych. Europejskie ograniczenia w zakresie realnych możliwości wojskowego oddziaływania w regionie, umniejszają szanse na efektywną kooperację obu podmiotów.
Trudne partnerstwo UE-NATO w latach 2017-2018
Keywords: European Union; NATO; defense policy; security; Unia Europejska; polityka obronna; bezpieczeństwo